The Audio Expert : everything you need to know about audio - Winer, Ethan (Routledge, 2018)
The Audio Expert is a comprehensive reference book covering all aspects of audio, with both practical and theoretical explanations. It is written for people who want to understand audio at the deepest, most technical level, but without needing an engineering degree. The Audio Expert explains how audio really works in much more depth than usual, using common sense plain-English explanations and mechanical analogies, with minimal math. It uses an easy to read conversational tone, and includes more than 400 figures and photos to augment the printed text.